Symptoms of depression at discharge after PCI are associated with an increased risk of 1-year mortality: findings from the national DenHeart study. (25th November 2020) - Borregaard, B; Nielsen, S.N; Lassen, J.F; Jensen, L.O; Thrysoe, L; Berg, S.K; Moller, J.E; Christensen, A.V; Ekholm, O; Mols, R.E; Thorup, C.B; Rasmussen, T.B
Abstract: Background: Although survival rates among patients with coronary artery disease have increased since the introduction of treatment with percutaneous coronary intervention, PCI, the effect of psychological factors such as symptoms of anxiety and depression on adverse outcomes are sparsely described. Purpose: The objective of the current study was to investigate the association between symptoms of anxiety and depression and 1-year mortality after PCI. Methods: A national cross-sectional survey at hospital discharge (responders, n=3, 366) with register-based follow-up among patients having undergone elective or emergency PCI. Mental health was measured using the Hospital Anxiety and Depression Scale, HADS, and divided into symptoms of anxiety (HADS-A) and symptoms of depression (HADS-D). The association between mental health (HADS-A and HADS-D) and 1-year all-cause mortality were investigated with Cox Proportional Hazard models with time to death as the underlying time scale. The results are presented as hazard ratios (HR) with 95% confidence intervals (CI) and adjusted for sex, age and Tu-comorbidity score. Results: At discharge, 32% of the population reported symptoms of anxiety (HADS-A ≥8) and 19% reported symptoms of depression (HADS-D ≥8). After one year, the mortality rate among patients being alive at discharge was 2.1%. All-cause mortality did not differ among patients reporting symptoms of anxiety compared to patients without symptoms of anxiety (2.3% vs 1.9%, p=0.454), whereas all-cause mortality was higher among patients reporting symptoms of depression compared to those, who did not (4.3% vs 1.6%, p≤0.001). In the regression analyses, symptoms of anxiety (HADS-A ≥8) was not associated with 1-year mortality (HR 1.16 95% CI 0.70–1.92); however, symptoms of depression was (HADS-D ≥8, HR 2.27 95% CI 1.38–3.73, adjusted analyses). Based on the continuous scores of HADS-D, a one-point increase in scores was associated with a 12% higher risk of 1-year mortality (HR 1.12 95% CI 1.05–1.18) (Figure 1). Conclusion: After PCI, nearly one-third of patient report symptoms of anxiety and one-fifth symptoms of depression. Symptoms of anxiety was not associated with 1-year mortality, whereas symptoms of depression increased the risk of 1-year mortality. Funding Acknowledgement: Type of funding source: None